Algeria qualifies for the World Cup between sporting competition and communication warfare - djefafla, Daoued (sports creativity, 2025)
The qualifying match for the 2010 World Cup was a high-stakes game for Algeria and its traditional rival, transforming it from a sporting event into a “media war” between the two sides, particularly on the part of the Algerian team's opponent. This research is an attempt to understand how the media, especially satellite channels, became involved in and dealt with this major sporting event. It seeks to identify the stakes behind this media identification with sport, the mechanisms it used, and the repercussions it had within and beyond the field of communication.